BUDAYA ORGANISASI PADA SEKOLAHMENEGAH KEJURUAN NURUL FALAH AUR KUNING KABUPATEN PASAMAN BARAT - Dita Salfitri (Jurnal Bahana Manajemen Pendidikan, 2014)
Phenomena in the field suggests that organizational culture in a state that has not been ideal. This study aimed to obtain information about organizational culture in vocational high school Nurul Falah Aur KuningKabupaten Pasaman Barat. This descriptive type of research. The population in this study were all teachers in vocational high school Nurul Falah Aur KuningKabupaten Pasaman Barattotaling 35 people. Sampling technique using proportionate stratifed random sampling technique. The research instrumen was a questionnaire likert scale models that have been tested for validity and reliability. In general, the department of education in organizational culture in vocational high schools Nurul Falah Aur Kuning Kabupaten Pasaman Barat quite well in the category with an average score of 3.99. Thus it can be said that the organizational culture is good. Key word: Organizational Culture